4=-6u-3

Rewrite the equation as -6u-3=4.

-6u-3=4

Multiply each term by u-3 and simplify.

Multiply each term in -6u-3=4 by u-3.

(-6u-3)⋅(u-3)=4⋅(u-3)

Cancel the common factor of u-3.

Move the leading negative in -6u-3 into the numerator.

-6u-3⋅(u-3)=4⋅(u-3)

Cancel the common factor.

-6u-3⋅(u-3)=4⋅(u-3)

Rewrite the expression.

-6=4⋅(u-3)

-6=4⋅(u-3)

Simplify 4⋅(u-3).

Apply the distributive property.

-6=4u+4⋅-3

Multiply 4 by -3.

-6=4u-12

-6=4u-12

-6=4u-12

Rewrite the equation as 4u-12=-6.

4u-12=-6

Move all terms not containing u to the right side of the equation.

Add 12 to both sides of the equation.

4u=-6+12

Add -6 and 12.

4u=6

4u=6

Divide each term by 4 and simplify.

Divide each term in 4u=6 by 4.

4u4=64

Cancel the common factor of 4.

Cancel the common factor.

4u4=64

Divide u by 1.

u=64

u=64

Cancel the common factor of 6 and 4.

Factor 2 out of 6.

u=2(3)4

Cancel the common factors.

Factor 2 out of 4.

u=2⋅32⋅2

Cancel the common factor.

u=2⋅32⋅2

Rewrite the expression.

u=32

u=32

u=32

u=32

u=32

The result can be shown in multiple forms.

Exact Form:

u=32

Decimal Form:

u=1.5

Mixed Number Form:

u=112

Solve for u 4=-6/(u-3)